14 Can we withdraw immunosuppressants in remitted patients?. (1st September 2020) - Zen, Margherita
Abstract : Remission has recently emerged as a potential target in the management of systemic lupus erythematosus (SLE), indeed remission is not uncommon and is associated with improved prognosis. 1 2 Nevertheless, the best management of remitted patients, especially those in stable remission, remains elusive. In particular, whether immunosuppressive therapy (IS) may be safely discontinued, without exposing remitted patients to a significant risk of flare, has not yet been clearly determined. Accordingly, available recommendations for the management of SLE underline the importance of progressive tapering of glucocorticoids (GCs) until withdrawal, but do not remark on the possibility of discontinuing IS in remitted patients. Moreover, the timing of IS discontinuation has not yet been established and in clinical practice it is quite common that remitted patients continue to receive the same treatment which led to remission, with the aim of preventing flares, for an indefinite period of time. It has been recently reported that ISs were safely withdrawn after remission achievement in more than 75% of patients with SLE in a cohort of 319 patients treated with IS for different manifestations, including lupus nephritis (LN) (47%), arthritis (15.7%), haematological abnormalities (5.3%), skin rash (6.3%), neuropsychiatric SLE (1.9%), vasculitis (1.3%), serositis (0.6%), and multi-organ involvement (21.9%). 3 The independent predictors of a safe discontinuation were hydroxychloroquine (HCQ) maintenance therapy after IS discontinuation and a longer duration of remission at IS discontinuation. Notably, being on HCQ and in remission for at least two consecutive years reduced the risk of flare by 81% and being on HCQ and in remission for at least three consecutive years by 86%. These findings are in keeping with recent recommendations, as antimalarials have been regarded as standard of care in all SLE patients unless contraindicated, including patients with LN, where antimalarials are proposed as an additional therapy. Interestingly, in this study maintenance therapy with 5 mg/day prednisolone equivalent alone did not protect against flares, as patients with low-dose maintenance therapy experienced a similar flare-rate compared to patients who discontinued all treatment at the time of IS withdrawal. In LN, different studies found a variable flare rate after IS discontinuation due to achievement of stable remission, ranging from 15% to 38.7%. Antimalarial therapy and a longer duration of remission at IS discontinuation resulted predictive of flare-free remission in some but not all these studies. Notably, the protective role of HCQ therapeutic levels against LN flares has recently been reported. 4 Indeed, among remitted patients, those with a subsequent renal flare during the follow-up had significantly lower HCQ levels compared with those in persistent remission. To date, different authors suggested a wide range of duration of IS maintenance therapy after remission achievement in LN, varying from 3 to 6.5 years. Based on available data, we can conclude that IS may be withdrawn in selected SLE patients, based on the characteristics of the individual patient, including their maintenance therapy and the duration of remission, which requires a personalised approach. In this regard, long-term therapy with antimalarials should be recommended in all SLE patients. 5 Continuous surveillance should be planned during treatment tapering and after withdrawal, to ensure any early signs or symptoms of disease relapse are detected. Learning Objectives: Explain why, although GCs should be de-escalated and withdrawn as early as possible in remitted patients, the timing of IS tapering until discontinuation in these patients is still an unresolved issue Describe the recent data suggesting that maintenance therapy with HCQ and a longer duration of remission at the time of IS withdrawal are protective against lupus flares Explain the importance of tight surveillance of lupus patients, during IS therapy tapering and after IS withdrawal in order to detect early signs or symptoms predictive of a disease relapse References: Zen M, Iaccarino L, Gatto M, et al . Prolonged remission in Caucasian patients with SLE: prevalence and outcomes. Ann Rheum Dis 2015;74(12) :2117–22. van Vollenhoven R, Voskuyl A, Bertsias G, et al . A framework for remission in SLE: consensus findings from a large international task force on definitions of remission in SLE (DORIS). Ann Rheum Dis 2017;76(3) :554–61. Zen M, Saccon F, Gatto M, et al . Prevalence and predictors of flare after immunosuppressant discontinuation in patients with systemic lupus erythematosus in remission. Rheumatology (Oxford) 2020;59(7) :1591–98. Cunha C, Alexander S, Ashby D, et al . Hydroxycloroquine blood concentration in lupus nephritis: a determinant of disease outcome? Nephrol Dial Transplant 2018 Sep 1;33(9) :1604–10. Gatto M, Zen M, Iaccarino L, Doria A. New therapeutic strategies in systemic lupus erythematosus management. Nat Rev Rheumatol 2019;15 :30–48.